Territoriality and playground disturbances : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Arts in Education - Anderson, Neil Alan (Massey University, 1973)
The concept of 'territoriality' has become a fairly common term within social scientific literature - and yet its application in the analysis of human behaviour appears to have been made with little reference to, or regard for, the concept's original form. The present investigation serves two purposes - first, to attempt to use the concept in the description and explanation of the etiology of social disturbances in school settings; and second, to look closely at the concept and assess its general worth in the analysis of human behaviour. Before investigating the possibility of a correlation between disturbances and the manifestation of territoriality, observations were made of the school pupil population during intervals to establish whether or not the pupils tended to occupy specific locations for protracted lengths of time - perhaps the most basic requisite of territorial behaviour. Observers gathered data in terms of the specific activities occurring and the sex and number of players. Time sampling was used, and the data confirmed that pupils do tend to return to the same geographical location to perform the same activity over a period of time. The stability of the pupil activity groups over time provided the foundation for a participant observer subsequently to investigate a second feature of territoriality - that territories are defended. The observer's task was to interview those involved in identified disturbances, and attempt to establish the etiology of the disturbance. The hypothesis was that the disturbances would be a function of the territorial behaviour of the groups. In so far as territorial behaviour can be defined in terms of Barker's (1968) 'maintenance mechanisms', the hypothesis was supported. 83% of disturbances were deemed to involve at least one feature of territoriality - be it membership, equipment, space, boundaries, or a combination of these. A further feature of the concept of 'territoriality' within animal behavioural research is that the territorial group members recognise each other on the basis of certain membership criteria. Within the pupil activity groups observed to investigate this feature among humans, membership criteria were also found to exist. These criteria were identified as being sex, class level, the amount of space available, family relationships, and physical size. On the basis of these criteria pupils were observed to be accepted or rejected from activity groups during school intervals. The findings of these initial investigations into the existence of three features of animal territoriality within human group behaviour, lend weight to an acceptance of the concept of territoriality as an adequate unit of analysis in the explanation of human group behaviour. However, throughout the investigations certain assumptions which underlie the concept tended to surface from time to time and raise doubts about the concept's applicability in human behavioural analysis. These assumptions included the idea that the territorial behaviour was manifested by members of both sexes; that territorial groups were family groups only; and that territorial behaviour was designed to repel intruders. All of these were shown in the present study to be not accurate. Added to these assumptions, the ethological literature reflects two crucial points of dissention. Ethologists, it seems, can not agree whether or not man is a territorial species. Again, among those who do accept that man is a territorial species, there is an argument over whether the territorial behaviour manifested by man is learned or instinctive. There are apparent problems in transferring a unit of analysis of animal behaviour to cover human behaviour as well. The problems are accentuated in the assumptions and debates outlined above, and compounded by the fact that within the social sciences there already exists a number of other theories and concepts which serve to explain the same human behaviour as territoriality attempts to do. While not completely rejecting the applicability of the concept of territoriality within human behavioural analysis, the conclusion arrived at was that the concept was of limited utility to the social scientist.
Keywords: Child psychology; Playgrounds